2017
DOI: 10.3390/su9050692
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on Connectivity and Perceived Values of Community Green Spaces

Abstract: Green spaces in residential communities are important yet understudied features of the urban ecological system. While large urban parks and remnant wildlands in urban areas tend to receive public attention from conservation and management perspectives, less is known about the importance of spatial and ecological characteristics of the community-scale green space. This study investigates natural elements in four planned communities in the Phoenix metropolitan area, Arizona; two of which represent conventional t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…The explanatory variables in this study included gender (male/female), age group (youth/mature), profession (farming/other than farming), literacy (illiterate/literate), and the area of residence (urban/peri-urban) of the respondents. These variables were chosen after a detailed review of the published literature [27,28,31,47]. A detailed analysis of the explanatory variables is presented in Table 2.…”
Section: Design Of the Survey Instrumentmentioning
confidence: 99%
“…The explanatory variables in this study included gender (male/female), age group (youth/mature), profession (farming/other than farming), literacy (illiterate/literate), and the area of residence (urban/peri-urban) of the respondents. These variables were chosen after a detailed review of the published literature [27,28,31,47]. A detailed analysis of the explanatory variables is presented in Table 2.…”
Section: Design Of the Survey Instrumentmentioning
confidence: 99%
“…Social benefits are associated with volunteering to maintain GI, and the, "composition, characteristics and mechanisms," by which these groups remain engaged in the decision-making processes of GI management and maintenance are evaluated (Jerome et al, 2017). An assessment of resident perception of green infrastructure in four communities in the Phoenix (Arizona, USA) area showed that respondents inhabiting communities with GI Water Environment Research, Volume 90, Number 10 -Copyright © 2018 Water Environment Federation have higher satisfaction than the people in conventional communities (Park, 2017). The management of urban green spaces by resident volunteers is discussed identifying three key factors for success 1) established rules and procedures within groups provide stability to citizens 2) citizens need to be able to adapt to contextual changes in order to cope with external political, socioeconomic and cultural developments over time and 3) the supporting role of authorities was also key to provide legitimization and support (Mattijssen et al, 2017).…”
Section: Waveform Airborne Laser Scanning (Lidar) Ismentioning
confidence: 99%
“…Evidence has shown that biodiversity is an important factor in influencing green space use and green spaces with higher biodiversity (such as variety in birds and richness in vegetation) are more likely to be visited [29]. In addition, the connectivity of green space is found to have a positive impact on the perception of greenness and safety [26]. Subsequently, it can improve the attractiveness of green space and induce green space use, to a certain degree.…”
mentioning
confidence: 98%
“…new green spaces or largely change the structure of existing urban green space systems to promote PGS use and physical activity [18,22,23]. Considering that, several researchers have argued that enhancing the connectivity of these green spaces by referring to the principals of landscape ecology is likely a relatively economical and efficient way to handle with the aforementioned challenges [22,24,25].In the urban context, well connected green spaces not only reflect more ecology and sustainability, contributing to improved residents' perception of well-being; but they also tend to increase the accessibility to green space system [26]. In other words, the connectivity of green space could improve the micro-climate, living environment, urban landscape quality, etc., which, in turn, has the potential to enhance green space use [27].…”
mentioning
confidence: 99%
See 1 more Smart Citation